Analysis on External Ballistic Characteristics of Rocket-assisted Equipment Launching on Surface Warship (Dandao Xuebao/Journal of Ballistics, 2023)
To research the influence of the launching conditions of surface warship on the external ballistic characteristics of rocket-assisted equipment,the warship-motion coordinate system and wind-field coordinate system were defined as well as centroil-motion coordinate system. The external ballistic equations and the parachute-projectile system model of rocket-assisted equipment were established considering ballistic conditions and meteorological conditions. By an example,the external ballistic characteristics of rocket-assisted equipment were analyzed under the influence of the sailing conditions and the sea wind conditions,and the coordinates of fall points under standard conditions and nostandard conditions were compared. The conclusion shows that the ballistic characteristics of rocket-assisted equipment are obviously affected by sailing speed and wind field. The deviation of fall-point coordinates can exceed the expected value under specified conditions,which can influence the efficiency of equipment.